2009
DOI: 10.1002/andp.200910384
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of polymer conductivity on the work function of metallic electrodes

Abstract: It is shown that the occurrence of metallic conductivity in polymers is due to their electrification. In particular, the current density depends on the electron work function of metallic electrodes which are in contact with the polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…For example, gold has an electron work function of about 4.7 eV. Thus, viewed composite films exhibit a low resistance on a gold substrate according to [22]. In fact, we see in present work the inverse situation.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…For example, gold has an electron work function of about 4.7 eV. Thus, viewed composite films exhibit a low resistance on a gold substrate according to [22]. In fact, we see in present work the inverse situation.…”
Section: Resultssupporting
confidence: 54%
“…It can be concluded that there is no relation between the conductivity of the RGO/polystyrene composite and the electron work function of substrate material, as was shown in [22]. For example, gold has an electron work function of about 4.7 eV.…”
Section: Resultsmentioning
confidence: 85%
“…The interest in the study of conducting polymers with dielectric properties can be explained by the possibility their use as components of electronic devices in various fields [1][2][3][4]. It is known [1][2][3][4][5][6][7][8] that thin films of dielectric polymers are able to conduct electricity below the electric field breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…It is known [1][2][3][4][5][6][7][8] that thin films of dielectric polymers are able to conduct electricity below the electric field breakdown. Whereas doped polymers have conductivity levels similar to semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…As polymers we used imid-siloxane, polyimide and polyamidine [8]. All investigated polymers were with defects.…”
Section: Introductionmentioning
confidence: 99%